2007
DOI: 10.1111/j.1423-0410.2007.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Early proliferation of umbilical cord blood cells from premature neonates

Abstract: These results suggest that the higher capacity of proliferation and early differentiation of premature UCB might not be related only to the amount of stem/progenitor cells but also to a different timing of cell cycle entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…These results do not support the viewpoint that CFUs are uncorrelated to fetal sex or that CFUs are related to gestational age. 8,13,24 Our results suggest that vaginal delivery and fetal weight have a positive influence on HQCBUs. We hypothesize that the distress response during vaginal delivery may increase cytokine levels, inducing primary cells to enter the fetal circulatory system and thus increasing the quantities of TNCCs, CD341 cells, and hematopoietic progenitor cells in CB.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These results do not support the viewpoint that CFUs are uncorrelated to fetal sex or that CFUs are related to gestational age. 8,13,24 Our results suggest that vaginal delivery and fetal weight have a positive influence on HQCBUs. We hypothesize that the distress response during vaginal delivery may increase cytokine levels, inducing primary cells to enter the fetal circulatory system and thus increasing the quantities of TNCCs, CD341 cells, and hematopoietic progenitor cells in CB.…”
Section: Discussionmentioning
confidence: 62%
“…Our results suggest that vaginal delivery and fetal weight have a positive influence on HQCBUs. We hypothesize that the distress response during vaginal delivery may increase cytokine levels, inducing primary cells to enter the fetal circulatory system and thus increasing the quantities of TNCCs, CD34+ cells, and hematopoietic progenitor cells in CB . Manegold and colleagues found that in the CB of women who gave birth via Cesarean section, cases with fetal distress had significantly higher TNCC, CD34+ cell count, and CFU‐GM compared to cases without fetal distress.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, younger gestational age was associated with lower post‐TNCC, due to the smaller size of the baby and resulting smaller CBU collection, but the collections from these younger babies were enriched for both CFUs and CD34+ cell content reflecting higher potency overall. Samples of CB from preterm infants have been shown in vitro to have higher concentration of hematopoietic progenitor cells (i.e., CFUs) in addition to increased proliferative potential compared to term infants . Previous studies have also found that CBUs derived from donors of younger gestational age have higher CFU and/or CD34+ content .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to cells isolated from umbilical cord blood (UCB) collected from premature neonate [49, 50] and to hAECs [44], oAECs obtained at early stage of gestation displayed a higher proliferative activity. As supposed for UCB derived cells, this aspect could be related to the larger amount of stem/progenitor cells, as well as, to a more rapid cell cycle required in preterm fetuses in order to drive an intense organogenesis [50].…”
Section: Discussionmentioning
confidence: 99%
“…As supposed for UCB derived cells, this aspect could be related to the larger amount of stem/progenitor cells, as well as, to a more rapid cell cycle required in preterm fetuses in order to drive an intense organogenesis [50]. The hypothesis of a larger aliquots of stem/progenitor cells in amniotic derived cells obtained from early amnia could be suggested by the higher expression of pluripotency markers, but not by the in vitro differentiation experiments.…”
Section: Discussionmentioning
confidence: 99%